Predicting Customer Loyalty of Local Brand Fast-Food Restaurant in Indonesia: The Role of Restaurant Quality and Price Fairness - Iwan Mulyawan; Khintan Evia Tulsi; Wahyu Rafdinal (Journal of Business and Management Review, 2022)
Recent research discusses the need for a better understanding of customer perceptions about fast-food restaurant attributes, such as qualities in influencing the process of customer satisfaction. This study aims to analyze the importance of quality in influencing loyalty in fast-food restaurants. The sample in this study is 247 respondents who have visited fast-food restaurants. Data are collected using a questionnaire survey that was done in around Bogor Raya. The analysis technique used is the Structural Equation Model with Partial Least Square. The structural equation model was applied to test 5 hypotheses. The results showed that food quality, service quality, and price fairness directly influence customer loyalty through customer satisfaction. Meanwhile, physical environment quality indirectly affects customer loyalty through customer satisfaction. This study provides a better understanding of restaurant quality, price fairness, customer satisfaction, and customer loyalty in fast-food restaurants. This study suggests that the quality of ethnic restaurants, such as food quality, service quality, and physical environment quality, can be valuable indicators for increasing customer loyalty through customer satisfaction and being an attractive marketing strategy for the preferences to increase customer loyalty for fast-food restaurant experiences.